Język opisu bibliograficznego jako język specjalistyczny - Tomaszczyk, Jacek; Gołda, Agnieszka (2024)
The bibliographic description language is both a type of information retrieval language and a special language that is used to create bibliographic descriptions for documents. Over the centuries, the ways of registering the features of documents reproduced in bibliographic descriptions have evolved. These descriptions are created by international bibliographic standards and citation styles, which are essential for bibliographers and authors of academic, popular science, and popular texts. The paper presents the theory of the language of bibliographic descriptions, its functions (cognitive, communicative, and search), vocabulary (paranatural notation with uncontrolled vocabulary), grammar rules, various methods of notation, and the diverse groups of users.
Keywords: language of bibliographic description; special language; bibliographic description; bibliographic method; bibliography